Unsupervised explorative data analysis of normal human leukocytes and BCR/ABL positive leukemic cells mid-infrared spectra1. Issue 13 (7th July 2015) - Bellisola, G.; Bolomini Vittori, M.; Cinque, G.; Dumas, P.; Fiorini, Z.; Laudanna, C.; Mirenda, M.; Sandt, C.; Silvestri, G.; Tomasello, L.; Vezzalini, M.; Wehbe, K.; et al.
<x xml:space="preserve">Abstract</x> Infrared microspectroscopy complemented with unsupervised principal component analysis is a suitable method to study protein phosphorylation/de-phosphorylation balance in cell models.